IMPROVING READING COMPREHENSION ABILITY THROUGH DIFFERENTIATED LEARNING - Maharatri, Kisma Arrum; Maryani, Ika; Saputri, Valynsa Milawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research aims to improve the reading comprehension skills of class III A students at SD Muhammadiyah Noyokerten through differentiated learning strategies for the 2022/2023 academic year. This type of research is Collaborative Classroom Action Research. The subjects in this research were class III A students at SD Muhammadiyah Noyokerten, totaling 17 students consisting of 07 male students and 10 female students. This research uses data collection techniques in the form of observation, interviews and tests. The data analysis technique uses qualitative and quantitative methods in the form of interactive data analysis consisting of data reduction, data presentation, and drawing conclusions. Qualitative data was obtained from interviews and observations. Meanwhile, quantitative data was obtained from the results of reading comprehension tests. The results of the implementation of cycle 1 and cycle 2 show that differentiated learning strategies can improve reading comprehension skills, the improvement is shown by 6 students or 35.29% completing the pre-action test. Then cycle 1 was carried out and the result was an increase of 11 students or 64.70%. In cycle 1 the indicators of success had not been achieved and cycle 2 was carried out. The test results in cycle 2 increased to 13 students or 76.47%.